A Review on Sustainable Approach for Production of Biodiesel from Waste Cooking Oil: A Case Study of Brunei Darussalam - Abdullah, Mas Fathasha; Melayu, Audrey Menti Baring Anak; Hassim, Faten Khairullisa Najihah; Tien, Ho Hao; Hamdani, Muhammad Hasbul Wafi Mohammad; Shin, Wong Yen; Bilad, Muhammad Roil (Jurnal Penelitian dan Pengkajian Ilmu Pendidikan: e-Saintika, 2023)
Biofuels like biodiesel and bioethanol are the latest technologies to meet the rising energy demand and to replace depleting petroleum supplies. Biodiesel, which is made from vegetable oils, can be used to replace diesel fuel. Vegetable oils are a sustainable energy resource with a similar energy content to diesel fuel. In the proposed process, the main product from the reaction is biodiesel, whereas the by-products consist of glycerol and fertilizer. Biodiesel is mainly used in automotive diesel engines for various reasons, such as having a greater oxygen content, a higher cetane number, a higher viscosity, a lower aromatic content, and very little sulfur. These properties are essential in engine performance, combustion, and emissions. This review provides a comprehensive analysis of recent literature on biodiesel production methods from waste cooking oil, where the methods are grouped systematically and assessed. A decision table on process selection is provided to screen the most suitable technology for biodiesel production from waste cooking oil. The properties and application of potential products and by-products are also discussed. Finally, the case study of supplying biodiesel for B5 fuel in Brunei Darussalam is also provided.